Fostering Innovation Through Creative and Collaborative Teaching Approaches: Menumbuhkan Inovasi Melalui Pendekatan Pengajaran yang Kreatif dan Kolaboratif - Yudianto, Nofit; Kurniawan, Bayu; Wijayanti, Ruri; Kholis, Nur (Universitas Muhammadiyah Sidoarjo, 2025)
Innovation in education is essential to prepare students for complex and dynamic future challenges. Specifically, in primary schools, the role of teachers in fostering an innovative culture is crucial but often underexplored. Despite existing studies on pedagogical innovation, limited research addresses how teachers in resource-constrained public schools actively drive innovation. This study aims to identify and analyze the role of teachers in cultivating a culture of innovation at SDN Kawengen 01 Ungaran Timur through a qualitative descriptive approach. The findings reveal that teachers serve as educators, facilitators, and motivators, effectively enhancing student creativity and collaborative skills. Results also show the consistent integration of project-based and collaborative learning models, coupled with the use of technology, despite limitations in training and infrastructure. A significant improvement was observed in the classroom’s learning environment, which became more conducive and experimental. The novelty of this study lies in highlighting bottom-up innovation efforts by teachers in public schools without relying heavily on systemic reforms. These findings imply the need for targeted professional development and the formulation of educational policies that support innovative practices in teaching. SDN Kawengen 01 emerges as a potential model for implementing creative and effective instructional strategies in similar educational contexts.Highlights: Highlights teacher-driven innovation in resource-limited settings. Emphasizes project-based and collaborative learning methods. Shows improved classroom environment through creative strategies. Keywords: Teacher Role, Innovation Culture, Creative Education, Teaching Strategy, Public Primary School